2022
DOI: 10.3390/plants11223112
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genome-Wide Analysis and Expression Pattern Profiling of PLATZ Gene Family Members in Solanum Lycopersicum L. under Multiple Abiotic Stresses

Abstract: PLATZ (plant AT-rich sequence and zinc-binding) family proteins with two conserved zinc-dependent DNA-binding motifs are transcription factors specific to the plant kingdom. The functions of PLATZ proteins in growth, development, and adaptation to multiple abiotic stresses have been investigated in various plant species, but their role in tomato has not been explored yet. In the present work, 20 non-redundant Solanum lycopersicum PLATZ (SlPLATZ) genes with three segmentally duplicated gene pairs and four tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
1
6
1
Order By: Relevance
“…This number is comparable to cabbage and higher than the numbers for Arabidopsis [ 17 ] and Ginkgo [ 26 ]. Compared to Wai’s [ 27 ] findings, which discovered 20 SlPLATZ genes, this is different. We found that Wai used a tomato assembly version other than Sl5.0 L., which may be the main reason for the disparity in the number of PLATZ genes.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…This number is comparable to cabbage and higher than the numbers for Arabidopsis [ 17 ] and Ginkgo [ 26 ]. Compared to Wai’s [ 27 ] findings, which discovered 20 SlPLATZ genes, this is different. We found that Wai used a tomato assembly version other than Sl5.0 L., which may be the main reason for the disparity in the number of PLATZ genes.…”
Section: Discussioncontrasting
confidence: 84%
“…Phylogeny is the study of the origin and evolutionary history of biological groups, each of which has its own origins and developmental history, regardless of its size. Along with the organisms we included together, I left out Amborella ( Amborella trichopoda ), moss ( Physcomitrella patens ), and green algae ( Chlamydomonas reinhardtii ) concerning Wai’s [ 27 ], but with Pennellii included. The PLATZ genes differed significantly depending on where the plant was in its evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drought-responsive element MBS motif was detected in the promoters of SlE2F/DP 6, SlE2F/DP 7 and SlE2F/DP 8 suggested their role in abiotic stress. These MBS elements were reported in HVA22 gene and PLATZ transcription factor against abiotic stress [ 39 , 40 ]. The ABRE cis-elements and the Meja responsive motif is abundant in SlE2F/DP genes.…”
Section: Discussionmentioning
confidence: 99%